Effectiveness of video-assisted teaching program on dental hygiene among children - Chatterjee, Lt. Col. Keka; Selvadhas, Lt. Col. Mary; R, Lt. Col Rajanimole; Sharma, Major Sarita; Shukla, Capt. Mahima (Indian Journal of Child Health, 2017)
Introduction: Worldwide, dental problems affect children’s health, causing millions of school hours to be lost each year. An effective community prevention program as a planned procedure prevents the onset of a disease among a group of individuals and the most cost-effective method is health education. Objectives: Assess the effectiveness of video-assisted teaching program on dental hygiene among primary schoolchildren. Methods and Materials: An experimental study was carried out in 60 primary schoolchildren between the age group of 5 and 10 years by dividing them into experimental and waitlisted control group. Pretest- post-test waitlisted control group design and simple random sampling were used. Standardized plaque index score and semistructured knowledge questionnaire used as tool. Results: The experimental group pre-test means rank (30.23) was significantly lower than the overall post-test rank (44.00) according to Mann–Whitney U-test. The control group pre-test means rank (30.77) was significantly higher than the post-test means rank (17.00) U = 442 (Z = ?0.118), p < 0.01. The difference between the experimental and waitlisted control group was large (? = 0.906). Conclusion: The level of awareness among schoolchildren regarding correct dental hygiene practices is low. The video-assisted teaching program was found to be effective in improving the dental hygiene of the schoolchildren as measured by plaque index score. The knowledge regarding the importance of maintaining dental hygiene will help more and more schoolchildren to follow the correct dental hygiene practices.